Complex‐Formation‐Enhanced Fluorescence Quenching Effect for Efficient Detection of Picric Acid. Issue 38 (31st July 2014) - Ding, Aixiang; Yang, Longmei; Zhang, Yuyang; Zhang, Gaobin; Kong, Lin; Zhang, Xuanjun; Tian, Yupeng; Tao, Xutang; Yang, Jiaxiang
Abstract Amine‐functionalized α‐cyanostilbene derivatives (Z)‐2‐(4‐aminophenyl)‐3‐(4‐butoxyphenyl)acrylonitrile (ABA) and (Z)‐3‐(4‐butoxyphenyl)‐2‐[4‐(butylamino)phenyl]acrylonitrile (BBA) were designed for specific recognition of picric acid (PA), an environmental and biological pollutant. The 1:1 host–guest complexes formed between the chemosensors and PA enhanced fluorescence quenching, thus leading to sensitive and selective detection in aqueous media and the solid phase.